Comparative productivity of indigenous sheep in the highland areas of Ethiopia and Rwanda - Gautsch, K.D. (International Livestock Centre for Africa, 1987)
Presents analysis of productivity in sheep production in the highlands of Ethiopia and Rwanda, w., particularly emphasis on the biological and environmental factors influencing the different productivity parameters, evaluation of reproductive and productive performance, comparison of productivity in the two countries and the responsibility of different sheep management systems being the main factor for different levels of productivity, w. suggestions for future improvement.